Bio-efficacy of growth regulator stance 110 SC on soybean (Glycine max L.): Bio-efficacy of growth regulator stance 110 SC on soybean (Glycine max L.) - S RAJAKUMARA (Journal of Oilseeds Research, 2020)
Plant height, no. of branches/plant, no. of pods/plant, seed yield and haulm yield were significantly greater with the application of growth regulators compared to control. Seed yield (1455 kg/ha) with the spray of stance 110 SC @ 150 ml/ha was on par with that of highest yielded treatment Chlormequat chloride 50% SL @ 500 ml/ha (1656 kg/ha).